The THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY LEVEL, DYSPNEA AND SLEEP QUALITY IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Gündoğan, Reva; GÜLER, Sevim; ÇORAPLI, Gökhan (Göbeklitepe Medical Science Journal, 2024)
The study was conducted to determine the relationship between physical activity level and dyspnea and sleep quality in patients with Chronic Obstructive Pulmonary Disease.The research was conducted in the form of a descriptive study with 128 patients who applied to the chest diseases polyclinic of an university training and research hospital between July 2022 and December 2022 and met the inclusion criteria of the study. The data of the study were collected with “Personal Information Form”, “International Physical Activity Questionnaire”, “Modified Borg Scale”, and “Chronic Obstructive Pulmonary Disease and Asthma Sleep Impact Scale”. Number, percentage, mean, Mann Whitney U, Kruskall Wallis, and Spearman correlation tests were used in the statistical analysis of the data. The Mann-Whitney U and dual post hoc tests were applied.There was a statistically significant difference between age and physical activity score, presence of an additional chronic disease and physical activity and sleep scale scores, marital status and dyspnea scale scores (p<0.05). In addition, a statistically significant difference was found between physical activity category mean scores and dyspnea and sleep scores (p<0.05). In the correlation analysis, it was found that as the physical activity level increased, dyspnea and sleep scale scores decreased, and as the dyspnea scale score increased, the sleep scale score increased (p<0.01).In order to reduce dyspnea and improve sleep quality of patients with Chronic Obstructive Pulmonary Disease, it is recommended that nurses include a programmed physical activity training plan in their nursing care plans, encourage patients and take care in implementing it.